Vacuum-assisted staged omphalocele reduction: A preliminary report - Nissen, Matthias; Romanova, Anna; Weigl, Elena; Petrikowski, Laura; Alrefai, Mohamad; Hubertus, Jochen (Frontiers in Pediatrics, 2022)
Introduction Omphalocele represents a rare congenital abdominal wall defect. In giant omphalocele, due to the viscero-abdominal disproportion, gradual reintegration of eviscerated organs is often associated with medical challenges. We report our preliminary experience combining staged gravitational reduction with vacuum (VAC) therapy as a novel approach for treatment of giant omphalocele. Patients and methods Retrospective chart review of six patients (five females) born between September 2018 and May 2022 who underwent staged reduction of giant omphalocele in conjunction with VAC therapy was conducted. Treatment was performed at two German third-level Pediatric Surgery Departments. Biometric and periprocedural data were assessed. Main outcome measure was the feasibility of VAC therapy for giant omphalocele. Data are reported as median and interquartile range (Q1–Q3). Results Gestational age was 37 (37–38) weeks, and birth weight was 2700 (2500–3000) g. VAC dressing was changed every 3 (3–4) days until abdominal fascia closure at the age of 9 (3–13) days. Time to first/full oral feeds was 3 (1–5)/20 (12–24) days with a hospital stay of 22 (17–30) days. Follow-up was 8 (5–22) months and complications were of minor extent (none: n = 2; Clavien–Dindo I: n = 3; Clavien–Dindo II: n = 1), comprising a delayed neo-umbilical cord rest separation (n = 2) and/or concomitant neo-umbilical site infection (n = 2) with no repeat surgery. Conclusion In neonates with giant omphalocele, VAC constitutes a promising and technically feasible enhancement of the staged gravitational reduction method. This study shows evidence that VAC may accelerate restoration of the abdominal wall integrity in giant omphalocele, thus minimizing associated comorbidities inherent to a prolonged hospitalization.